Theoretical and experimental studies of an effective active vibration control method based on the deflection shape theory and optimal algorithm. (1st May 2022) - Sun, Yuhan; Song, Zhiguang; Li, Fengming
Highlights: Inspired by the mode localization, an active vibration control method is proposed. The concept of destructive interference is introduced in active vibration control. The present active control method is applicable for arbitrary frequency vibrations. Abstract: Similar to mode shapes, deflection shapes are distributions of vibration amplitudes on structures under non-resonant excitations. Therefore, they are also essential vibration characteristics of structures. This paper proposes an effective active vibration control method under both non-resonant and resonant excitations based on the deflection shape theory and optimal algorithm. Taking the vibration isolation of an object on a flat plate as an example, the active vibration control method is illustrated. Piezoelectric patches are used as sensors and actuators. The main idea of the present vibration control method is to construct the suitable deflection shapes according to the position of the object by using the genetic algorithm (GA). There are two methods to select the desired deflection shapes. Under non-resonant external excitations, the desired deflection shapes are assumed artificially based on the idea of mode localization. While under resonant excitations, the desired deflection shape will be determined by the concept of destructive interference, that is, it should be completely opposite to the original one. In order to make the structure vibrate according to the desired deflection shape, piezoelectric materials are used to obtain the active loads or stiffness. The optimal actuating voltages and feedback control gains in the active control will be determined by GA. The effects of these active vibration control methods are investigated through the theoretical analyses, numerical simulations, as well as experimental verifications. These results demonstrate that the present active control method is effective.